Adiposity and risk of thyroid cancer: a systematic review and meta‐analysis. Issue 12 (14th September 2015) - Schmid, D.; Ricci, C.; Behrens, G.; Leitzmann, M. F.
Summary: Thyroid cancer incidence has increased rapidly over time, as has obesity prevalence. A link between the two appears plausible, but the relation of adiposity to thyroid cancer remains incompletely understood. We performed a meta‐analysis of adiposity measures and thyroid cancer using studies identified through October 2014. Twenty‐one articles yielded data on 12, 199 thyroid cancer cases. We found a statistically significant 25% greater risk of thyroid cancer in overweight individuals and a 55% greater thyroid cancer risk in obese individuals as compared with their normal‐weight peers. Each 5‐unit increase in body mass index (BMI), 5 kg increase in weight, 5 cm increase in waist or hip circumference and 0.1‐unit increase in waist‐to‐hip ratio were associated with 30%, 5%, 5% and 14% greater risks of thyroid cancer, respectively. When evaluated by histologic type, obesity was significantly positively related to papillary, follicular and anaplastic thyroid cancers, whereas it revealed an inverse association with medullary thyroid cancer. Both general and abdominal adiposity are positively associated with thyroid cancer. However, relations with BMI vary importantly by tumour histologic type.